Air [videorecording (Blu-Ray)] - Affleck, Ben, 1972-; Convery, Alex; Damon, Matt; Bateman, Jason; Messina, Chris; Maher, Matthew (Actor); Wayans, Marlon; Mohr, Jay; Tennon, Julius, 1953-; Tucker, Chris, 1972-; Davis, Viola (Warner Bros. Entertainment, 2023)
From award-winning director Ben Affleck, it reveals the unbelievable game-changing partnership between a then-rookie Michael Jordan and Nike's fledgling basketball division which revolutionized the world of sports and contemporary culture with the Air Jordan brand. This moving story follows the career-defining gamble of an unconventional team with everything on the line, the uncompromising vision of a mother who knows the worth of her son's immense talent, and the basketball phenom who would become the greatest of all time.